Totalization speculative practice in architectural education - Schaum, Troy (Park books, 2019)
Totalization for the first time offers a comprehensive and richly illustrated insight into Rice Architect's Totalization Studios - one of the most innovative architectural teaching programs worldwide. In close collaboration with renowned consultants, four studios challenge conventions around structures, façades, materials, and the mechanical aspects of building design and construction. Through featured projects complemented by essays and conservations with faculty members and consultants, Totalization explores these studios, and interrogates how practitioners can leverage the breadth of architectural practice toward in-depth speculative design work. Architecture is the quintessential generalist pursuit. An architect's expertise, first and foremost, lies in understanding the big picture - in totalization.